Visual Analytics for Linked Open Data in Marine Sciences - Nuñez, Gustavo (2022)
The purpose of data exploration and data visualization (DV) is to offer ways of perceiving and manipulating information, as well as extracting and inferring knowledge. In this short paper we present advances in visual representations and intuitive interaction techniques based on artificial intelligence. This contributes significantly to the exploration and understanding of information related to marine sciences represented by ontologies and linked data. This preliminary research allows scientists and non-expert users to analyze sets with information related to oceanography, meteorology and environmental parameters to promote scientific knowledge and productive innovation in the South Atlantic ocean using Linked Open Data (LOD).